2014
DOI: 10.1007/s13277-014-2467-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of squamous cell carcinoma antigen-immunoglobulin M complex (SCCA-IGM) and alpha-l-fucosidase (AFU) as novel diagnostic biomarkers for hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) surveillance lacks a reliable biomarker. Alpha-fetoprotein (AFP) is the most widely used. However, not all HCCs secrete AFP. AFP may be elevated with cirrhosis in the absence of HCC. Serum alpha-L-fucosidase (AFU) and squamous cell carcinoma antigen-immunoglobulin M complex (SCCA-IgM) were found to be useful markers in diagnosing HCC. SCCA-IgM and AFU were assessed by ELISA technique; AFP was measured by enzyme chemiluminescence in serum of 40 patients with HCC, 30 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
3
19
1
Order By: Relevance
“…The clinical utility of high-sensitivity AFP-L3 (hs-AFP-L3) in early prediction of HCC development in patients with chronic HBV or HCV infection was recently evaluated in a large Japanese study. Even at low AFP levels and in absence of suspicious ultrasound findings an elevation of hs-AFP-L3 was an early predictor of HCC development with an elevation in 34.3% of patients one year prior to diagnosis of HCC [27] . In patients with low AFP levels (< 20 ng/mL), the diagnostic sensitivity for hs-AFP-L 3% at a cut-off of 5% was 41.5% with a specificity of 85.1% [28] .…”
Section: Role Of Biomarkers In Surveillance and Diagnosismentioning
confidence: 92%
“…The clinical utility of high-sensitivity AFP-L3 (hs-AFP-L3) in early prediction of HCC development in patients with chronic HBV or HCV infection was recently evaluated in a large Japanese study. Even at low AFP levels and in absence of suspicious ultrasound findings an elevation of hs-AFP-L3 was an early predictor of HCC development with an elevation in 34.3% of patients one year prior to diagnosis of HCC [27] . In patients with low AFP levels (< 20 ng/mL), the diagnostic sensitivity for hs-AFP-L 3% at a cut-off of 5% was 41.5% with a specificity of 85.1% [28] .…”
Section: Role Of Biomarkers In Surveillance and Diagnosismentioning
confidence: 92%
“…Hepatocellular carcinoma (HCC) is the sixth most prevalent cancer and the third most frequent cause of cancer-related death, and over 80 % of HCC cases occur in developing countries [1][2][3]. Worldwide, HCC is a leading cause of cancerrelated mortality and has a very poor prognosis because it is rarely diagnosed at an early stage; moreover, the burden of this devastating cancer is expected to increase further in coming years [4].…”
Section: Introductionmentioning
confidence: 99%
“…(Table ) The major bias identified in the studies was in “patient selection” and the “index test”. Four studies selected cirrhosis patients as the control group; seven studies included patients with hepatitis, chronic liver disease, or cirrhosis or healthy donors as the control group . Three studies did not included tumour biopsies to confirm HCC, and we marked one study as “unclear” …”
Section: Resultsmentioning
confidence: 99%
“…Lately, the progressive increase in SCCA and immunoglobulin M (SCCA‐IgM) has been associated with liver tumour development, suggesting that monitoring SCCA‐IgM levels might be useful for identifying cirrhotic patients at higher risk of developing HCC . Two studies performed in two different countries with distinct populations confirmed that SCCA and SCCA‐IgM levels have better diagnostic accuracy than AFP for the diagnosis of HCC . Moreover, a number of studies supported the usefulness of SCCA‐IgM for the diagnosis, prognosis and monitoring of chronic liver disease, including the histological response after antiviral treatments .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation